Deciphering charge transfer dynamics of a lead halide perovskite-nickel(ii) complex for visible light photoredox C-N coupling - Kumar V.; Patel S.K.; Vyas V.; Kumar D.; Subramaniam Iyer E.S.; Indra A. (My University, 2025)
Photoredox catalysis involving perovskite quantum dots (QDs) has gained enormous attention because of their high efficiency and selectivity. In this study, we have demonstrated CsPbBr3 QDs as photocatalysts for the C-N bond formation reaction. The introduction of Ni(dmgH)2 (dmgH = dimethyl glyoximato) as a cocatalyst with CsPbBr3 QDs facilitates photocatalytic C-N coupling to form a wide variety of amides. The optimized interaction between the cocatalyst and photocatalyst enhances charge transfer and mitigates charge recombination, ultimately boosting photocatalytic performance. The photocatalytic activity is notably influenced by the variation in the amount of cocatalyst and 7 wt% Ni(dmgH)2 produces the best yield (92%) of amide. Femtosecond transient absorption spectroscopy reveals that the dynamics of the trap states of QDs are affected by cocatalyst. Further, Ni(dmgH)2 facilitates molecular oxygen activation to form superoxide radicals, which further initiates the radical pathway for the C-N coupling. © 2024 The Royal Society of Chemistry.